Drawing with shear as an effective method of the control of the structure and the properties for low-carbon steel - Pashinskaya, E.; Zavdoveev, A.; Varyukhin, V.; Tkachenko, V.; Maksakova, A.; Alekseenko, I. (Физика и техника высоких давлений, 2015)
Technology of drawing with shear has been developed for manufacturing of low-carbon steel wire without annealing. It has been established that a specific feature of the presented technology is a reduction of the structure anisotropy and an increase in the plasticity resource. This effect is associated with shear that forces a change of the metal flow direction. Розроблено технологію волочіння зі зсувом для виготовлення дроту з низьковуглецевої сталі без відпалу. Встановлено, що особливістю запропонованої технології є зниження анізотропії структури та збільшення ресурсу пластичності. Цей ефект пов’язаний зі зсувною деформацією, яка викликає зміну напрямку течії металу. Разработана технология волочения со сдвигом для изготовления проволоки из малоуглеродистой стали без отжига. Установлено, что особенностью предлагаемой технологии являются снижение анизотропии структуры и увеличение ресурса пластичности. Этот эффект связан со сдвиговой деформацией, которая вызывает изменение направления течения металла.